Tailoring the climate security observatory to livestock-related conflicts - Orenstein, Alex; Liebig, Theresa Ines (CGIAR FOCUS Climate Security, 2022)
The Climate Security Observatory (CSO) is a decision support tool helping policymakers and other practitioners to understand and respond to climate-related security risks. It currently covers broad aspects of the climate security nexus, describing overall relationships among the dimensions of climate, conflict and socioeconomic vulnerabilities over a multiannual timeframe, without in-depth analysis of specific components around e.g. livestock-related conflicts, migration aspects, or food systems. This report is meant to guide future work that includes livestock systems into the CSO. To visualize agro-pastoral conflict and understand its causes, factors and exacerbators, the general CSO questions, analysis and used data sources need to be tailored to livestock systems. The report will therefore review current CSO analysis and give recommendations on how to include livestock systems and pastoral conflicts.